Development and validation of a booklet based on health literacy on medicinal teas for women breast cancer survivors (Research, Society and Development, 2021)
Aim: To describe the process of construction and validation of a booklet on teas with medicinal properties, aimed at women survivors of breast cancer, prepared according to the fundamentals of health literacy. Method: Methodological study carried out in three stages: 1) interview with women survivors of breast cancer to identify the teas most used by them; 2) development of the booklet and 3) validation of the booklet by specialists and target audience. From the information of the 203 women interviewed, five plants were selected to integrate the booklet: Graviola (leaf), Chamomile, Mint, Ginger and Pomegranate. The content of the booklet was developed according to scientific knowledge on the subject and guidelines of specific publications on health literacy, with the aim of enabling greater empowerment of information by women. The validation was carried out by six specialists, who used the Suitability Assessment of Material (SAM) instrument, aimed at evaluating written materials according to the fundamentals of health literacy. Validation by the target audience was done by focus group. Results: The specialists attributed to the booklet an average percentage score of 91.4%, which makes it a superior material in terms of health literacy (70-100%). The target audience approved the booklet, with no suggestion of changes. Conclusion: The booklet is validated and meets the fundamentals of health literacy and can be used in the care provided to women who are survivors of breast cancer as an educational material to assist in their treatment.